2021
DOI: 10.1016/j.ajoc.2021.101195
|View full text |Cite
|
Sign up to set email alerts
|

Transient vision loss associated with paracentral acute middle maculopathy detected on multi-modal imaging

Abstract: Purpose To report two patients with transient decreased vision and associated paracentral acute middle maculopathy (PAMM) lesions identified with multi-modal imaging, including what we believe to be the first documented patient of PAMM associated with iron deficiency anemia. Observations Case 1 is a 56-year-old man who experienced transient blurred vision one week following cardiac ablation for atrial fibrillation. Symptoms resolved by the time of presentation and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Our finding of unchanged VT in any comparison supports the idea that RIPLs reflect chronic lesions similar to PAMM lesions. Prior case reports of PAMM have demonstrated that qualitative changes in tortuosity in PAMM generally follow a pattern of occasional acute increases in tortuosity21 22 that sometimes progressively worsen23 but that eventually improve 24…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of unchanged VT in any comparison supports the idea that RIPLs reflect chronic lesions similar to PAMM lesions. Prior case reports of PAMM have demonstrated that qualitative changes in tortuosity in PAMM generally follow a pattern of occasional acute increases in tortuosity21 22 that sometimes progressively worsen23 but that eventually improve 24…”
Section: Discussionmentioning
confidence: 99%